Plastic Legacies Pollution, Persistence, and Politics - Farrelly, Trisia; Taffel, Sy; Shaw, Ian (Athabasca University Press, 2021)
There is virtually nowhere on Earth today that remains untouched by plastic and ecosystems are evolving to adapt to this new context. While plastics have revolutionized our modern world, new and often unforeseen effects of plastic and its production are continually being discovered. Plastics are entangled in multiple ecological and social crises, from the plasticization of the oceans to the embeddedness of plastics in political hierarchies. The complexities surrounding the global plastic crisis require an interdisciplinary approach and the materialities of plastic demand new temporalities of thought and action. Plastic Legacies brings together scholars from the fields of marine biology, psychology, anthropology, environmental studies, Indigenous studies, and media studies to investigate and address the urgent socio-ecological challenges brought about by plastics. Contributors consider the unpredictable nature of plastics and weigh actionable solutions and mitigation processes against the ever-changing situation. Moving beyond policy changes, this volume offers a critique of neoliberal approaches to tackling the plastics crisis and explores how politics and communicative action are key to implementing social, cultural, and economic change.